Business Audit in a Framework of ESG: Dialectic of Basic Categories of Verification Development - R. P. Bulyga; I. V. Safonova (Учёт. Анализ. Аудит, 2022)
Implementation of integrated thinking principles in the accounting and control environment expands the boundaries of traditional ideas about the formation and confirmation of the reporting information reliability — from financial statements to business practice data. Based on the analysis of global trends in international and domestic initiatives for ESG reports development, the authors substantiate the conclusion that it is necessary to form a new architecture of corporate reporting verification regulations. As the study results, the paper presents the current standards of auditing from the point of view of regulating the procedure for substantiating and expressing by the auditor confidence provided to the interested user to increase confidence in the auditor’s opinion (inference). The research revealed trends in the type’s expression of confidence in the certification of public reports of companies in Russian and international practice. The authors tried to define approaches to the definition and classification of the terms verification, certification, confirmation and audit. They have been based on the level of confidence provided to the user, as well as the methodology used for obtaining evidence by the verifier. The authors highlighted the need for further development of business audit as an effective way to find a balance between the commercial interests of audit firms and the demand for reliable, transparent business information from society and stakeholders. The outcomes got will expand audit practice in implementing the concept of sustainable development and introducing ESG principles into the business processes of companies. The study may interest national regulators, professional communities, as well as investors and financial market participants.